2013
DOI: 10.1093/pcp/pct088
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis COPT6 Transport Protein Functions in Copper Distribution Under Copper-Deficient Conditions

Abstract: Copper (Cu), an essential redox active cofactor, participates in fundamental biological processes, but it becomes highly cytotoxic when present in excess. Therefore, living organisms have established suitable mechanisms to balance cellular and systemic Cu levels. An important strategy to maintain Cu homeostasis consists of regulating uptake and mobilization via the conserved family of CTR/COPT Cu transport proteins. In the model plant Arabidopsis thaliana, COPT1 protein mediates root Cu acquisition, whereas CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…Furthermore, analysis of the COPT1, COPT2 and COPT6 promoter regions reveals multiple putative light and circadian cis-regulatory elements. 9,17,18 Some of these motifs are involved in phytochrome regulation of gene expression, 19 which corroborates the reduction of COPT2 transcript in the phy mutants. 15 Such cis-responsive elements could also participate in the regulation of the transcriptional factor SPL7, as they are found in its promoter (Fig.…”
Section: Plasma Membrane High Affinity Copper Transport Is Under Lighsupporting
confidence: 64%
“…Furthermore, analysis of the COPT1, COPT2 and COPT6 promoter regions reveals multiple putative light and circadian cis-regulatory elements. 9,17,18 Some of these motifs are involved in phytochrome regulation of gene expression, 19 which corroborates the reduction of COPT2 transcript in the phy mutants. 15 Such cis-responsive elements could also participate in the regulation of the transcriptional factor SPL7, as they are found in its promoter (Fig.…”
Section: Plasma Membrane High Affinity Copper Transport Is Under Lighsupporting
confidence: 64%
“…Whereas aerial COPT6 transcript upregulation by Cu deficiency is fully dependent on SPL7, its regulation in roots seems to be partially independent of the SPL7 transcription factor [12]. We observed that contrary to COPT1 and COPT2, COPT6 expression is also present under Cu-sufficient conditions [48]. Our analyses of endogenous Cu levels have shown that the copt6 knock-out lines do not exhibit a significant defect in total Cu accumulation under either Cu-sufficient or Cu-deficient conditions.…”
Section: The Copt6 Protein Facilitates Cu Distribution In Aerial Tissuesmentioning
confidence: 55%
“…We observed that, with the exception of COPT4, the ectopic expression of all the Arabidopsis COPT family members expressed in yeast Cu transport mutants stimulates Cu uptake and accumulation [12,13,49]. Regarding yeast growth complementation, COPT1, COPT2, and COPT6 fully rescued the ctr1Δctr3Δ defect under nonfermentable and low Fe conditions, whereas the COPT3 and COPT5 effect was only partial [6,12,13,48]. We observed that COPT4 expression, which does not possess the key methionine residues essential for Cu transport, including the MX 3 M motif, proves toxic to yeast cells [13].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations